An introduction to multivariate statistical analysis - Anderson, Theodore Wilbur (A John Wiley & Sons, Inc., Publication, 2004)
Perfected over three editions and more than forty years, this field- and classroom-tested reference: * Uses the method of maximum likelihood to a large extent to ensure reasonable, and in some cases optimal procedures ; * Treats all the basic and important topics in multivariate statistics ; * Adds two new chapters, along with a number of new sections ; * Provides the most methodical, up-to-date information on MV statistics available.